Novi pristopi pri vodenju kariere, ki izhajajo iz teorije socialnega učenja - Drobnič, Janez (Šolsko polje, 2012)
Rapid changes in technological development, particularly information technology and globalization have demanded a response and the accelerate development of new theories and approaches in the field of career guidance and career counseling, which is largely rooted in the theory of social learning. Theory and practical approaches to career guidance, resulting from social learning theories emphasize certain features of this process through symbolic expressions and phrases, which can be recognized as accidental design situations, wrapping, openness to change, activity, flexibility and responsiveness. Therefore the contribution in particular has been to bring a range of methods and techniques to both the individual and the collective, the individual's training and learning to cope with uncertainty and to manage their own careers in a time of rapid change. Social learning theory has become an obvious starting point for theories and approaches to career development in modern time. It offers a set of useful tools to cope successfully with the change and implementation of the dynamic career of each individual. However, this does not mean we one should discard other theories and tools in favour of Parsons' theory of characteristics and requirements that is now current model as a comparison between work and private individuals. Likewise, we cannot conceive of good professional decisions without Holland instruments establishing the suitability of jobs that fall within the framework of differential theories. Also, development theory, which was founded by D. Super and laid out in the way of today's guidance, is still relevant. In addition, it is still necessary to determine the professional / employment goals, a good knowledge of self and environment (the labour market) as well as counseling and teaching techniques. All of these "classical theories" combined with the new, form a wide range of theoretical approaches and practical methods of vocational decision-making and career counseling in a dynamic time.
Keywords: career guidance; poklicno usmerjanje; poklicno svetovanje; risk-taking; positivity; pozitivnost; kariera; Kariera people; plan happenstance; social learning; socialno učenje; vzgoja in izobraževanje; education